X-ray non-detection of PSR J0250 + 5854. Issue 4 (14th February 2023) - Tan, C M; Rigoselli, M; Esposito, P; Stappers, B W
ABSTRACT: We conducted a deep XMM–Newton observing campaign on the 23.5-s radio pulsar PSR J0250 + 5854 in order to better understand the connection between long-period, radio-emitting neutron stars and their high-energy-emitting counterparts. No X-ray emission was detected resulting in an upper limit in the bolometric luminosity of PSR J0250 + 5854 of <10 31 erg s −1 for an assumed blackbody with a temperature of 85 eV, typical of an X-ray Dim Isolated Neutron Star (XDINS). We compared the upper limit in the bolometric luminosity of PSR J0250 + 5854 with the known population of XDINSs and found that the upper limit is lower than the bolometric luminosity of all but one XDINS. We also compared PSR J0250 + 5854 with SGR 0418+5729, the magnetar with low dipole magnetic field strength, where the upper limit suggests that if PSR J0250 + 5854 has a thermal hotspot like SGR 0418 + 5729, it would have a blackbody temperature of <200 eV, compared to 320 eV of the magnetar.